2016
DOI: 10.3934/ipi.2016033
|View full text |Cite
|
Sign up to set email alerts
|

Model-based reconstruction for magnetic particle imaging in 2D and 3D

Abstract: We contribute to the mathematical modeling and analysis of magnetic particle imaging which is a promising new in-vivo imaging modality. Concerning modeling, we develop a structured decomposition of the imaging process and extract its core part which we reveal to be common to all previous contributions in this context. The central contribution of this paper is the development of reconstruction formulae for MPI in 2D and 3D. Until now, in the multivariate setup, only time consuming measurement approaches are ava… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 44 publications
(80 reference statements)
0
31
0
Order By: Relevance
“…A first step towards a theoretical understanding of this problem, while excluding the temporal dependence, can be found in [39]. A one-dimensional problem setup considering the time-dependency of the measurements was analyzed in [11] for one particular trigonometric excitation.…”
Section: Appendix Iii: Magnetic Particle Imaging (Mpi)mentioning
confidence: 99%
“…A first step towards a theoretical understanding of this problem, while excluding the temporal dependence, can be found in [39]. A one-dimensional problem setup considering the time-dependency of the measurements was analyzed in [11] for one particular trigonometric excitation.…”
Section: Appendix Iii: Magnetic Particle Imaging (Mpi)mentioning
confidence: 99%
“…MPI is a new biomedical imaging modality that images the distribution of SPIONs. Some researchers adopt mathematical models to describe the physical process, like the equilibrium model [ 25 ] or its variations, the x-space approach [ 3 , 26 , 27 , 28 ], Chebyshev polynomials [ 29 ], and analytic inversion formulas [ 30 , 31 ]. The state-of-the-art reconstruction techniques adopt the experimentally calibrated forward operators, called the SM-based image reconstruction [ 32 , 33 ].…”
Section: The Theory Of Sm-based Mpimentioning
confidence: 99%
“…The average NRMSE of all frequency components is around 10%. In 2017, Marz performed mathematical modeling on the reconstruction of two-dimensional and three-dimensional MPI and obtained a reconstruction formula different from one-dimensional [ 30 ]. In the same year, Knopp described the basic principles of MPI imaging, including signal generation, spatial coding, and signal detection [ 37 ].…”
Section: The Theory Of Sm-based Mpimentioning
confidence: 99%
“…The mathematical study on the MPI model is fairly scarce. The only work on FFP trajectories that we are aware of is the work [31]. In a 1D setup with FFP trajectories moving along a line for the equilibrium model, the authors [31] showed that in the limit of large particle diameters, the integral kernel is a Diracdelta function, and thus the imaging problem is well-posed.…”
Section: Introductionmentioning
confidence: 99%
“…The only work on FFP trajectories that we are aware of is the work [31]. In a 1D setup with FFP trajectories moving along a line for the equilibrium model, the authors [31] showed that in the limit of large particle diameters, the integral kernel is a Diracdelta function, and thus the imaging problem is well-posed. Further, they analyzed a related problem which is independent of the FFP trajectory used, under the assumption that each spatial point is scanned multiple times with nonparallel trajectories.…”
Section: Introductionmentioning
confidence: 99%